Insights into meningioangiomatosis with and without meningioma: A clinicopathologic and genetic series of 24 cases with review of the literature - (:unkn) unknown (WILEY, 2005)
Meningioangiomatosis (MA) is a rare seizure-associated lesion of presumed hamartomatous or developmental origin. It is occasionally combined with a neoplasm, most commonly meningioma (MA-M). In the current study, we examined 24 cases (14 pure MA, 10 MA-M) using immunohistochemistry for merlin, protein 4.1B, progesterone receptor (PR), and MIB-1, as well as FISH for NF2 and 4.1B gene dosages. Nine cases of MA-M (90%) had gene deletions (NF2/4.1B), protein losses (merlin/protein 4.1B), and/or PR positivity, with a similar or identical phenotype in both components. No PR positivity or gene deletions were seen in pure MAs, though merlin and/or protein 4.1B were immunonegative in six cases. Our data suggest that in most MA-Ms, the MA component is neoplastic, likely representing an exuberant perivascular pattern of spread from the meningioma, rather than an underlying hamartoma. This pattern of spread may be facilitated by meningiomas that are predominantly leptomeningeal or intracerebral in origin. It remains important to distinguish this pattern from true brain invasion, given the more ominous prognostic significance of the latter. In contrast, most perivascular spindled cells of pure MA are genetically and immunohistochemically similar to non-neoplastic meningothelial cells, consistent with current histogenetic theories.
Keywords: VON RECKLINGHAUSENS DISEASE; CLEAR-CELL MENINGIOMA; INTRAPARENCHYMAL MENINGIOMA; MENINGEAL TUMORS; UNDERLYING MENINGIOANGIOMATOSIS; CEREBRAL MENINGIOANGIOMATOSIS; HISTOPATHOLOGIC CORRELATION; VONRECKLINGHAUSENS DISEASE; SCLEROSING MENINGIOMA; MR FINDINGS